2005
DOI: 10.1158/1535-7163.mct-05-0031
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase inhibitor MMI-166 inhibits lymphogenous metastasis in an orthotopically implanted model of lung cancer

Abstract: Matrix metalloproteinases (MMP) are considered to be critically involved in tumor invasion and the metastasis of various cancers. MMI-166 is a selective inhibitor of matrix metalloproteinase (MMP-2, MMP-9, and MMP-14). The purpose of this study was to evaluate the effects of MMI-166 on both the growth of the implanted tumor and the lymph node metastasis of the mediastinum and prolonging the life span, using an orthotopic implantation model of the Ma44-3 cancer cell line. We examined the anti-invasive effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…Arrows and circles in the picture indicate the localization of detectable, mediastinal lymph nodes and tumor mass, respectively. 36 Despite the presence of the primary lung tumor responsible for cancer cells spreading to the mediastinum, Gem-C12 LNCs only localized in mediastinum lymph nodes were able to exert the same antitumor efficacy as the systemic administration of Gem-C12 (loaded in LNCs or micelles) (Figure 2, A), which exerted a systemic anticancer activity (i.e., on primary lung tumor and therefore on the spreading of mediastinal metastases) and resulting in the increase of the survival lifespan to the same extent (Figure 2, A). Moreover, this similar survival improvement by targeting only lymph nodes was also accompanied by lower systemic side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Arrows and circles in the picture indicate the localization of detectable, mediastinal lymph nodes and tumor mass, respectively. 36 Despite the presence of the primary lung tumor responsible for cancer cells spreading to the mediastinum, Gem-C12 LNCs only localized in mediastinum lymph nodes were able to exert the same antitumor efficacy as the systemic administration of Gem-C12 (loaded in LNCs or micelles) (Figure 2, A), which exerted a systemic anticancer activity (i.e., on primary lung tumor and therefore on the spreading of mediastinal metastases) and resulting in the increase of the survival lifespan to the same extent (Figure 2, A). Moreover, this similar survival improvement by targeting only lymph nodes was also accompanied by lower systemic side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Significant inhibition of breast cancer metastases in brain was achieved in a rat model when animals were treated with a synthetic inhibitor (PD 166793) [107]. In animals that received a selective MMP inhibitor against MMP-2, MMP-9 and MMP-14 (MMI-166), a significant decrease was shown for lymph node metastasis from lung carcinoma [108]. Overall, the results of these MMP inhibition studies indicated a beneficial effect of early administration of MMP inhibitors, a notion which became apparent after evaluation of clinical trials in cancer patients.…”
Section: Mmp Inhibition Targeting Angiogenesismentioning
confidence: 99%
“…It is an MMP-2, -9 and -14 selective inhibitor that spares MMP-1, -3 and -7. While it has shown anticancer activity in numerous animal models of human cancer (including implanted lung cancer, melanoma, squamous carcinoma, colon and cervical) [64,65], there are no data as to its clinical performance. The key structural feature exemplified by MMI-166 is the "deep" aryl (here, a triaryl) substitution.…”
Section: New Generation Hydroxamate-based Mmp Inhibitorsmentioning
confidence: 99%